2021
DOI: 10.2147/ndt.s306596
|View full text |Cite
|
Sign up to set email alerts
|

Association of Reduced Tract Integrity with Social Communication Deficits in Preschool Autism Children: A Tract-Based Spatial Statistics Study

Abstract: Purpose To analyze the changes in white matter tracts in preschool children with autism spectrum disorder (ASD), and the correlation between these changes and social communication deficits. Methods Diffuse tensor imaging was used to assess white matter integrity using tract-based spatial statistics in a sample of 50 right-handed children with ASD aged 2–6 years vis a reference sample of 46 typically developing children aged 2–6 years. We then correlated these significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In our study, RMET score correlated significantly with the FA values of areas implicated in social cognition as well as tracts involved in motor function (the corticospinal tract, CST). It was recently reported that children with autism spectrum disorder (ASD) exhibited reduced FA in the CST compared to typically developing children [33] . We suggest that this association between CST and ToM may reemerge with aging.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, RMET score correlated significantly with the FA values of areas implicated in social cognition as well as tracts involved in motor function (the corticospinal tract, CST). It was recently reported that children with autism spectrum disorder (ASD) exhibited reduced FA in the CST compared to typically developing children [33] . We suggest that this association between CST and ToM may reemerge with aging.…”
Section: Discussionmentioning
confidence: 99%